Possible Antidepressant Effects of Memantine-Systematic Review with a Case Study - Marek Krzystanek; Stanisław Surma; Artur Pałasz; Monika Romańczyk; Krzysztof Krysta (MDPI AG, 2021)
The treatment of bipolar depression is hampered by the inadequate efficacy of antidepressants, moderate effect of mood stabilizers, and the side effects of some second-generation antipsychotics. There is limited evidence to date regarding the antidepressant effects of memantine in bipolar depression. The aim of the article was to provide a short review of preclinical and clinical studies on the antidepressant effect of memantine, and to present the case of a bipolar depression patient successfully treated with memantine. The described patient with bipolar disorder was unsuccessfully treated with two mood stabilizers. The addition of memantine at a dose of 20 mg/d to the treatment with lamotrigine and valproic acid resulted in a reduction in the severity of depression measured on the HDRS-17 scale by 35%, and by 47.1% after 7 weeks. The discussion presents experimental evidence for the antidepressant effect of memantine, as well as data from clinical trials in recurrent and bipolar depression. The presented case is the second report in the medical literature showing the antidepressant effect of memantine as an add-on treatment for bipolar depression. The described case and literature analysis indicate that memantine may be an effective and safe method of augmentation of mood stabilizing therapy in bipolar depression.